(untitled) (Bangladesh Journal of Medical Education, 2024)
Background: In last few decades, there was a trend in medical sector observing with more female admitted into different medical colleges of Bangladesh. So, this research was aimed to investigate the extent of feminization of medical education in Bangladesh. Methods: This descriptive type of cross-sectional study was conducted from July’22 to June’23. Data was collected through reviewing the document to find the extent of feminization in last 15 years. Results: Out of 73481 seats, 40567 (55.21%) female and 32914 (44.79%) male were admitted in different Government, Non-Government and Armed Forces Medical Colleges of Bangladesh over 10years period. Considering the total number of students graduated, out of 42597 students, 22763 (53.44%) female and 19834 (46.56%) male graduated from different Government, Non-Government and Armed Forces Medical Colleges of Bangladesh. Out of 35993 MBBS graduates registered in Bangladesh Medical & Dental Council (BM&DC), 18411 (51.15%) male and 17582 (48.85%) female were registered. Conclusion: The findings of this research hoped to find out the future impact of extent of feminization of medical education on health care delivery system of Bangladesh and possible ways to overcome from such situation. BJME, Volume-15, Issue-01, January 2024: 49-56